Analysis of Object and Attractiveness of Community-Based Ecotourism in Coastal Area of Mempawah Regency - Eva Dolorosa; Dewi Kurniati (Agro Ekonomi, 2019)
Mangrove ecotourism in the Mempawah coastal area began to be developed and initiated by local communities who are concerned in the sustainability of the mangrove ecosystem. This is also supported by the increasing number of tourists to visit ecotourism, so that the development of ecotourism needs to be supported by tourist attractiveness as well as learning to tourists to care about their environment in accordance with the principles of ecotourism namely responsible travel to natural areas, conserving the environment and improving the well-being of local people. This paper focuses on analyzing the potential value of community-based ecotourism objects and its attractiveness. The assessment indicator based on the guidelines for assessment of natural tourism attractiveness was used to assess the objects and attractiveness in three specific ecotourism locations which are managed by local communities in Mempawah, namely Pasir, Bakau, and Mendalok Village. This study involves the participation of tourists who have visited the  ecotourism site. The study found that the potential value of the object and attractiveness mangrove ecotourism in Mempawah Area was 3,105 with an average score of 388 meaning that it ispotentially developed, and also increasing recommendations related to community-based ecotourism development.